DEVELOPMENT AND CHARACTERIZATION OF IONIC LIQUID LOADED HALLOYSITES NANOCONTAINERS FOR SMART PH-RESPONSIVE ANTICORROSION COATINGS - YAP, JEN YANG (2021)
Epoxy coating applied to material surfaces to prevent corrosion is susceptible to damages, creating a discontinuity in the coating layer leading to corrosive material exposure. The smart pH-responsive coating can prolong the coating’s service life, allowing less maintenance and reducing cost. In this study, a smart pH-responsive coating was produced by loading 1-butyl-3-methylimidazolium chloride [Bmim][Cl] into the halloysite nanotubes (HNTs) and encapsulated with polyelectrolytes via layer-by-layer technique. The [Bmim][Cl] release was studied using Ritger–Peppas and Korsmeyer–Peppas model. The pH-responsivity of the loaded HNTs was controlled by surface charges of the polyelectrolyte layer. Combination of weak/weak polyelectrolytes; poly(ethylenimine) (PEI) and poly (acrylic acid) (PAA) has shown sensitive behavior towards pH stimulus and released the [Bmim][Cl] more effectively compared to the combination of strong/weak polyelectrolytes of poly (diallyl dimethylammonium hydrochloride (PDADMAC) and poly (acrylic acid) (PAA). Further analysis on combination of PEI and PAA polyelectrolytes layers showed the best responsiveness towards pH stimulus when assembled under 0.5M NaCl solution, achieving total release of 14.74% (pH 7), 40.66% (pH 4) and 53.27% (pH 10) at the 72 hours of immersion. The corrosion study of the loaded HNTs in epoxy was conducted using Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization (PD). EIS and PD results revealed that defected epoxy with addition of the HNTs-[Bmim][Cl](PEI, PAA) has a higher charge transfer resistance, lower corrosion current density with inhibition efficiency of 60.65% (EIS) and 87.84% (PD) after one hour immersion and maintained throughout 72 hours immersion. The SEM images and EDX proved the existence of [Bmim][Cl] and the corrosion activity on steel was suppressed.